A turn-on fluorescent probe for hydrogen sulfide and its application in living cells. Issue 105 (13th October 2015) - Zhao, Miao; Li, Hua; Li, Hui; Qiao, Qinglong; Cao, Cheng; Xu, Zhaochao
Abstract : Herein, we described a probe for H2 S detection based on the reduction of azide to amine. This probe was highly sensitive and selective toward H2 S and successfully applied for H2 S fluorescent imaging in living cells. Abstract : Hydrogen sulfide (H2 S) is an important endogenous signalling molecule in cellular physiology and pathology. Accordingly, sensitive, selective and reliable methods for H2 S detection are in high demand. Fluorescence-based methods thus have received great attentions in recent years. Herein we describe the design, synthesis and application of a probe for H2 S detection based on the reduction of azide to amine. This probe is highly sensitive and selective toward H2 S over biothiols and other biologically relevant species. Finally, the probe was successfully applied for H2 S fluorescent imaging in living cells.